1992
DOI: 10.1111/j.1399-0004.1992.tb03630.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Silver‐Russell syndrome and translocation (17;20) (q25;q13)

Abstract: Ramírez‐Dueñas ML, Medina C, Ocampo‐Campos R, Rivera H. Severe Silver‐Russell syndrome and translocation (17;20)(q25;q13). Clin Genet 1992:41: 51–53. An 8‐year‐8‐month‐old girl with Silver‐Russell syndrome (SRS) and a paternally inherited balanced t(17;20)(q25;q13) is described. This observation suggests that an SRS gene(s) maps on chromosome 17 or 20 and that the patient phenotype resulted from either unmasking of heteroz‐ygosity or genomic imprinting via paternal disomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
5

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 6 publications
0
7
0
5
Order By: Relevance
“…Apart from patients with duplication 11p15 (n = 15), microdeletion 12q14 (n = 19), ring chromosome 15, and deletion 15qter, at least 30 patients with various other chromosomal rearrangements (10 deletions, 9 duplications, and 11 other aberrations) have been reported (Tables –). Two patients from the group with various chromosomal rearrangements carry a balanced translocation (one paternally inherited 17;20 translocation and one de novo 1;17 translocation) [Ramírez‐Dueñas et al, ; Midro et al, ]. In six patients with duplication 11p15, additional most likely clinically relevant imbalances were described [Fisher et al, ; Eggermann et al, ; South et al, ; Bliek et al, ; Hu et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from patients with duplication 11p15 (n = 15), microdeletion 12q14 (n = 19), ring chromosome 15, and deletion 15qter, at least 30 patients with various other chromosomal rearrangements (10 deletions, 9 duplications, and 11 other aberrations) have been reported (Tables –). Two patients from the group with various chromosomal rearrangements carry a balanced translocation (one paternally inherited 17;20 translocation and one de novo 1;17 translocation) [Ramírez‐Dueñas et al, ; Midro et al, ]. In six patients with duplication 11p15, additional most likely clinically relevant imbalances were described [Fisher et al, ; Eggermann et al, ; South et al, ; Bliek et al, ; Hu et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…According to ISCN/HGVS the balanced translocation 46,XX,t(17;20)(q25;q13)pat (Ramírez‐Dueñas, Medina, Ocampo‐Campos, & Rivera, ) is described for der(17) as g.[chr17:pter_cen_(70900001_qter)::chr20:(41700001_qter)_qter and for der(20) as g.[chr20:pter_cen_(41700001_qter)::chr17:(70900001_qter)‐qter]. 70900001_qter is the coordinate for chromosome band 17q25, which also includes 17qter and the exact breakpoint is not known.…”
Section: Curation Of the Databasementioning
confidence: 99%
“…Analysis of genes in this region did not lead to the identification of a candidate gene involved in the syndrome. Various other chromosomal abnormalities have been described, including trisomy 1q32.1-q42.1 (van Haelst et al 2002), deletion of chromosome 15q or ring chromosome 15 (Rogan et al 1996), 18pϪ (Christensen and Nielsen 1978), translocations involving breakpoints 17q25 (Ramirez-Duenas et al 1992) and 17q23-24 (Dorr et al 2001), and, finally, a paternally inherited deletion of the CSH1 gene at chromosome 17q22-24 (Eggermann et al 1998). , Fisher et al (2002 reported three patients with a phenotype that includes growth retardation.…”
mentioning
confidence: 99%